Synthetic and spectrometric investigation of 1,4-benzoxazepines - Whittal, R D (Rhodes University, Faculty of Science, Department of Chemistry, 1990)
Flavanone (2,3-dihydro-2-phenyl-4H-benzopyran-4-one) and a series of 4'- and 7-halogeno derivatives were prepared from the corresponding 2'-hydroxychalcones [1-(2-hydroxyphenyl)-3-phenyl-2-propen-l-ones], which, in turn, were synthesized by aldol condensation of substituted 2'-hydroxacetophenones with various benzaldehydes. A series of 2,3-dihydro-2-phenyl-l,4-benzoxazepin-5(4H)-ones were prepared by ring expansion of the corresponding flavanones, via the Schmidt reaction, using trimethylsilylazide and trifluoroacetic acid. A series of tetrazoles {2,3-dihydro-2-phenyl-tetrazolo[1,5-d]-1,4-benzoxazepines} were also isolated as by-products of the Schmidt reaction. Flavanone oxime was synthesized for use in Beckmann reactions, and its molecular structure was determined by x-ray crystallography. Attempts to prepare 1,4-benzoxazepinone or its 1,5-analogue via Beckmann rearrangement of flavanone oxime, with polyphosphoric acid or phosphorus pentachloride catalysts, however, were unsuccessful. Several methods for introducing Î”Â²-unsaturation into the benzoxazepinone system were also examined. High resolution Â¹H n.m.r., computer modelling, and molecular mechanics techniques were used to determine the conformations of the heterocycles of the benzoxazepinones and tetrazoles and results are compared with earlier studies in this field. Certain trends in the fragmentation patterns were observed in the low resolution mass spectra of the benzoxazepinones and tetrazoles, and high resolution mass spectrometric data were used to explore the major fragmentation patterns of these compounds.
Keywords: Spectrum analysis; Benzodiazepines